Chicken soup for the soul : think positive : 101 inspirational stories about counting your blessings and having a positive attitude - Canfield, Jack 1944- (Chicken Soup for the Soul Pub., 2010)
A collection of 101 true personal stories from regular people about the power of positive thinking in their lives and how they use positive thinking, count their blessings, and are grateful.